David J. Lewis-Williams and David G. Pearce, San Spirituality: Roots, Expressions and Social Consequences; Sarah C. Brett-Smith, The Making of Bamana Sculpture: Creativity and Gender: Speaking of Spirits (Historia, 2021)
Within the almost infinite range of practices and beliefs that are available for cultural and historical analysis, those related to the "other world" remain the most elusive of all. Not that it has discouraged researchers from trying every possible theoretical angle, from Cultural History to post-postmodernism and from the most detached objectivism to total subjective submersion. In this review essay, I will compare two very similar, but also divergent attempts at capturing the essence of indigenous, African spiritual experience. The analysis of the authors of San Spirituality and The Making of Bamana Sculpture centres on the social category of the "artist-shaman", from a perspective which they themselves label "interpretive". Both texts provide great teaching material for a variety of classroom applications : material culture studies, sociology of knowledge, comparative religion, gender studies, heritage studies, the fieldwork paradigm, contemporary debates and more.